Some measures taken by Japanese small and medium enterprises in the recent two decades to promote research and development activities and suggestions for Vietnam - Anh, Vu Tuan; Dich, Tran Xuan (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
The article briefly analyzed some key challenges for research and development (R&D) of Japanese small and medium enterprises (SMEs)2 in recent two decades, including the funding and human resource development issues. Then, some solutions were presented in the paper to remedy obstacles and promote R&D activities of Japanese SMEs. Finally, based on those lessons learnt, some recommendations were made to promote R&D of SMEs in Vietnam. Keywords: Code: 16052301<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;">